2012
DOI: 10.4274/mirt.165
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m Labeled HMPAO white Blood Cell Scintigraphy in Pediatric Patients

Abstract: Objective: 99mTc labeled hexamethylpropylene amine oxime (HMPAO) white blood cell (WBC) scintigraphy is a frequently used option for acute infection, particularly in pediatric patients. This scintigraphy is applied to detect sites of infection/inflammation in patients with fever of unknown origin, to find and follow up osteomyelitis, and to detect suspicion of acute appendicitis. The aim of this retrospective study was to evaluate the value of 99mTc-HMPAO labeled WBC scintigraphy in pediatric patients.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Approaches to visualise these infiltrating cells and therefore to image inflammation have been performed via radiolabelled white blood cells (WBC) and it has been shown that autologous leukocytes radiolabelled with either 99m Tc-HMPAO or 111 In-oxine for SPECT or 18 F-FDG or 64 Cu for PET, respectively, specifically are enriched in inflamed tissues [ 32 34 ]. In fact, this is an established clinical procedure used in many different pathologic settings such as Crohn's disease [ 35 ], osteomyelitis [ 36 ], fever of unknown origin, infection [ 37 ], acute appendicitis [ 38 ], and arterial and colonic inflammation [ 39 ].…”
Section: Ex Vivo Labelling Of Leukocytesmentioning
confidence: 99%
“…Approaches to visualise these infiltrating cells and therefore to image inflammation have been performed via radiolabelled white blood cells (WBC) and it has been shown that autologous leukocytes radiolabelled with either 99m Tc-HMPAO or 111 In-oxine for SPECT or 18 F-FDG or 64 Cu for PET, respectively, specifically are enriched in inflamed tissues [ 32 34 ]. In fact, this is an established clinical procedure used in many different pathologic settings such as Crohn's disease [ 35 ], osteomyelitis [ 36 ], fever of unknown origin, infection [ 37 ], acute appendicitis [ 38 ], and arterial and colonic inflammation [ 39 ].…”
Section: Ex Vivo Labelling Of Leukocytesmentioning
confidence: 99%
“…(99m)Tc-HMPAO-labeled WBC scintigraphy is a frequently used option for acute infection. In one small study, (99m)Tc-HMPAO labeled WBC scintigraphy was found to be true positive in six cases, true negative in six cases, and false negative in one patient who had a fever of unknown origin (31). Ubiquicidin 29-41 (UBI 29-41) is a synthetic antimicrobial peptide fragment reported to be highly infection-specific.…”
Section: Osteomyelitis In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…To determine the localization, extent and severity of inflammation, imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) can be performed but have limitations in the early stages of the disease, as they are dependent on morphological changes [16][17][18]. Accurate and early diagnosis of inflammation and infection helps reduce mortality and morbidity and increase drug treatment success [19][20][21].Proinflammatory effects help leukocytes migrate from the blood vessel to the site of injury, due to increased vascular permeability through stimulation by cytokines and interleukins. There is an initial accumulation of granulocytes, mainly neutrophils, in the inflamed area and later of lymphocytes and macrophages [22][23][24].…”
mentioning
confidence: 99%
“…To determine the localization, extent and severity of inflammation, imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) can be performed but have limitations in the early stages of the disease, as they are dependent on morphological changes [16][17][18]. Accurate and early diagnosis of inflammation and infection helps reduce mortality and morbidity and increase drug treatment success [19][20][21].…”
mentioning
confidence: 99%